Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Di Wisma Flamboyan Rsj Prof. Dr. Hb. Sa’anin Padang - Syahira Hayati Yusrineza; Dwi Happy Anggia Sari; Vivi Yuderna; Ramaita . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hallucinations are a client's false perception through the five senses of an environment without any real stimulus or stimulation. According to WHO data from 2023, the prevalence of mental disorders worldwide was 970 million individuals worldwide. This data increased in 2024 to exceed 1.1 billion people. This increase in prevalence confirms that the global burden on mental health is increasingly severe. Based on initial data obtained from Prof. HB. Saanin Mental Hospital, Padang, the most common problem in 2025 was hallucinations, with 6,062 patients. This study aims to implement Mental Health Nursing Care for Mr. K with Hallucinations at Wisma Flamboyan, Prof. HB. Saanin Mental Hospital, Padang. The implementation of Nursing Care for Mr. K was conducted on February 4 to February 10, 2025 with a visit of six days of meetings. The method of this Scientific Paper is a Case Study. The results of the provision of Mental Nursing Care were obtained that Mr. K was able to control Hallucinations independently by using the implementation strategy (SP), namely SP 14. In this study, it is expected that Mr. K understands the provision of Mental Nursing Care and the client is able to control hallucinations independently and signs of hallucination symptoms decrease.